Vnutrisemejnoe schodstvo i regional'naja prinadležnost' sportsmenov vysokogo klass - Vorobyov, T. V.; Vostroknutova, E. M.; Khorosheva, O. A.; Pogudin, S. M. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Through a questionnaire survey of high-class athletes (members of the teams of the Perm region and the Russian Federation in athletics, martial arts, skiing and biathlon) revealed the degree of family heredity in the development of physical potential in pairs "parents - children"; analyzed regional affiliation (taking into account the number of inhabitants of the village) of these athletes. The results of the study confirm and Supplement the data of scientific and methodological literature on genealogical conditioning in the development of motor abilities of highly qualified athletes.